The Influence of Occupational Safety and Health (K3) on Employee Performance PT. Belawan Indah - Rachmawati, Yeni; Surbakti, Eka Wulandari; Triastuti, Neni; Ria, Vellia Puspita (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
This study discusses the effect of Occupational Safety and Health (K3) on the performance of employees of PT Belawan Indah. Lack of safety at work is certainly very dangerous for employees while working because it can cause unwanted things, for example, such as rarely using PPE (Personal Protective Equipment). The purpose of this study was to determine how occupational safety and health (K3) affects employee performance at PT Belawan Indah. This study uses 2 (two) variables, namely the independent variable Occupational Safety and Health (X) and the dependent variable Employee Performance (Y). The population amounted to 46 respondents with saturated sampling technique, where the entire population was used as a sample in this study, namely 46 people. The method used is quantitative method. The conclusion of the results of this study is the result of a simple linear regression of 0.405 with a constant of 20.382, which means that the two variables have a positive effect, the results of the t test show Thitung (3.657)> Ttabel (2.013), so it has an effect on variable Y (Employee Performance), while based on the coefficient of determination test there is an R Square value of 0.233 = 23.3%, so the Occupational Safety and Health variable (X) affects the Employee Performance variable (Y) by 23.3%.